EFFECTS OF CHRONIC METHYLPHENIDATE ON DOPAMINE/SEROTONIN INTERACTIONS IN THE MESOLIMBIC DOPAMINE SYSTEM OF THE MOUSE - Brookshire, Bethany (Wake Forest University, 2010)
Methylphenidate (MPH) is one of the most commonly prescribed drugs in the United States. MPH is a psychostimulant that inhibits the dopamine (DA) and norepinephrine (NE) transporters to increase extracellular monoamines. Abuse rates of MPH are increasing as prescription rates increase, but the effects of high-dose, chronic MPH exposure have not been well defined. In particular, the effects of MPH on serotonin (5-HT) systems have not been well investigated. While MPH itself does not have affinity for the 5-HT transporter, DA and 5-HT systems have many points of interaction, particularly in the mesolimbic DA system, an area associated with the rewarding and reinforcing properties of drugs. Thus, our studies focused on the interactions of DA and 5-HT systems at the level of the ventral tegmental area (VTA) and nucleus accumbens (NAc) following chronic MPH treatment in mice. The experiments utilized locomotor activity measures, conditioned place preference, single and dual probe in vivo microdialysis, radioligand binding, and behavioral tests for depressive like behaviors to examine the effects of chronic MPH. Our studies showed that chronic MPH alters DA/5-HT system interactions in the mesolimbic DA system. The alterations are such that elevations in 5-HT produced a stronger influence over DA neuron firing. Specifically, we found that the serotonin agonist fluoxetine increased DA in the NAc and produced place preference in MPH treated animals. Further investigations traced these changes to the VTA, where increasing 5-HT in the VTA produced increased DA cell firing when stimulated. Our studies subsequently examined which 5-HT receptors are responsible for this change. Of the five 5-HT receptors examined using locomotor activity, conditioned place preference, and in vivo microdialysis, the 5-HT1A and 1B receptors showed sensitization, and it appears that alterations in these receptors are primarily responsible for the influence of 5-HT over the DA system following MPH exposure. Finally, these studies have determined that chronic MPH produced depressive-like effects during withdrawal, and behavioral and neurochemical sensitization following exposure. Taken together, the investigations conducted in this thesis showed novel effects of MPH on 5-HT/DA interactions, with implications for the consequences of MPH abuse in humans.
Keywords: Dopamine; Serotonin; Methylphenidate; Cocaine; Fluoxetine; Nucleus Accumbens; Ventral Tegmental Area; 5-HT1B receptor